2021
DOI: 10.1093/ibd/izab333
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Colitis Is Associated With a Reduced Risk of Colorectal Adenoma and Cancer: A Meta-Analysis

Abstract: Background The study sought to conduct a systematic review and meta-analysis of the risk of colorectal adenoma or cancer in patients with microscopic colitis (MC). Methods A comprehensive literature search of PubMed and EMBASE databases was performed. Pooled relative risks (RRs) and 95% confidence intervals (CIs) were calculated to examine the effect of MC on the risk of colorectal adenoma or cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…There has been interest in the risk of colon cancer. Despite long-term inflammation, the risk of colon cancer seems to be decreased or similar to the background population in numerous epidemiological studies [44]. Thus, the increased risk of colonic cancer in patients with chronic long-term inflammation depends on the cause of inflammation, which unfortunately is not yet known.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…There has been interest in the risk of colon cancer. Despite long-term inflammation, the risk of colon cancer seems to be decreased or similar to the background population in numerous epidemiological studies [44]. Thus, the increased risk of colonic cancer in patients with chronic long-term inflammation depends on the cause of inflammation, which unfortunately is not yet known.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Although several studies have demonstrated an association between Crohn’s disease and ulcerative colitis and the risk of colorectal cancer ( Beaugerie and Itzkowitz, 2015 ; Olén et al, 2020b ; Olén et al, 2020a ), previous studies focusing on the risk of colorectal cancer in microscopic colitis have not revealed such an association ( Loreau et al, 2019 ; Levy et al, 2019 ; Borsotti et al, 2021 ). A systemic review and meta-analysis of 12 studies comprising 50,795 patients with microscopic colitis even found a lower risk of colonic adenomas and colorectal cancer ( Liu et al, 2021 ). Nevertheless, a Swedish nationwide, population-based cohort study recently examined the association between microscopic colitis and overall risk of cancer as well as of some important cancer subtypes ( Bergman et al, 2020 ).…”
Section: Prognosismentioning
confidence: 99%